Agro-morphological and Molecular Assessment of Advanced Wheat Breeding Lines for Grain Yield, Quality and Rust Resistance - Kumar, Satish; Sandhu, Geeta; Yadav, S S; Pandey, Vanita; Prakash, Om; Verma, Ajay; Bhardwaj, S C; Chatrath, Ravish; Singh, G P (Journal of Cereal Research, 2019)
The genetic gain for yield in wheat and other cereals has been known to be stagnating in recent years. Breeding wheat cultivars with increased genetic potential can contribute to meet at least half of the desired production increases. In this context, we have developed some advanced wheat lines in our breeding program, which aims to utilize the untapped variability. We assessed a set of 60 diverse lines along with four commercial check varieties for various agro-morphological traits, grain quality and yield based and also the adaptability using molecular markers. Significant genotypic differences were observed for most of the grain quality and agro-morphological traits recorded, including grain yield. We could identify lines which have significantly higher grain yield. The diversity analysis carried out using the DNA markers could explain the variability of different traits in this set. This set of genotypes is thus a very useful source as far as enhancing the yield levels. The lines developed through the conventional breeding program were based on crosses between elite breeding lines and specific donors and hence might result in higher yield potential. Â DOI.org/10.25174/2249-4065/2019/90162